Monitoring yeast autolysis in sparkling wines from nine consecutive vintages produced by the traditional method. (5th December 2021) - Pons‐Mercadé, P.; Giménez, P.; Vilomara, G.; Conde, M.; Cantos, A.; Rozès, N.; Ferrer, S.; Canals, J.M.; Zamora, F.
Abstract: Background and Aims: Yeast autolysis is a key step in the production of sparkling wines using the traditional method and a source of polysaccharides, mannoproteins and proteins. The evidence, however, of the enrichment of these macromolecules during ageing is not evident in the literature. In this study, autolysis of yeast lees in sparkling wines (Cava) was monitored over nine consecutive vintages. Methods and Results: The concentration of polysaccharides and proteins did not clearly increase over time, probably because these macromolecules are simultaneously released from lees and removed by other processes. In a new approach, the autolytic process was reproduced, and involved recovering the lees and maintaining them in a model wine solution for 1 year. The lees released polysaccharides and proteins, but only a small proportion of that found in the sparkling wines, especially in younger wines. Conclusions: This study confirmed that yeast enrich sparkling wines in key macromolecules but in low proportion in comparison with the usual concentration present in sparkling wine. This aspect should be considered by wineries that aim to achieve autolysis attributes, since the majority of sparkling wines are commercialised after short periods of ageing. Significance of the Study: This study determined for the first time the true contribution of yeast autolysis to the total polysaccharide and protein concentration of sparkling wines from nine consecutive vintages.